First of all you need to expand this expression. you do this by multiplying the number outside the brackets with each term inside the brackets. this is the first one ; 3 x 2a = 6a, 3 x 5 = 15. the extra + sign in the first brackets stays between the two terms, so the first set of brackets is now 6a + 15. now we have to look at the second ; 5 x a = 5a, 5 x 2 = 10, like the extra + sign, the extra - sign stays between the two terms as well, so the second bracket is now 5a-10. you put them together to get 6a + 15 + 5a - 10.
next you need to simplify the expression. first you need to group like terms, e.g. the numbers and the letters. 6a + 15 +5a -10. the 6a + 5a = 11a and the 15 - 10 = +5. you then put these two terms together to get your final answer of
11a + 5